Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE), 2014 2014
DOI: 10.7873/date.2014.248
|View full text |Cite
|
Sign up to set email alerts
|

Advanced system on a chip design based on controllable-polarity FETs

Abstract: Abstract-Field-Effect Transistors (FETs) with on-line controllable-polarity are promising candidates to support next generation System-on-Chip (SoC). Thanks to their enhanced functionality, controllable-polarity FETs enable a superior design of critical components in a SoC, such as processing units and memories, while also providing native solutions to control power consumption. In this paper, we present the efficient design of a SoC core with controllable-polarity FET. Processing units are speeded-up at the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Also new solutions to build sequential circuits as proposed by Gaillardon et al [19], [26] have to be found.…”
Section: -Bit Full Adder Design Examplesmentioning
confidence: 99%
“…Also new solutions to build sequential circuits as proposed by Gaillardon et al [19], [26] have to be found.…”
Section: -Bit Full Adder Design Examplesmentioning
confidence: 99%
“…Dense regular arrays of such cells can be fabricated, which are consecutively hard programmed by the metallization to the desired gate functionality. Doing so, it is possible to design logic circuits in a more compact memory array-like style, increasing the layout regularity [38,62]. From those patterns a transmission gate 1-bit full adder with only 14 transistors including input inverters can be built.…”
Section: Logic Circuits With Reconfigurable Field Effect Transistorsmentioning
confidence: 99%
“…Employing MIGFETs also a fully static 1-bit adder implementation amounting to a total of 18 transistors is possible [9,54]. Also first designs of more complex combinational and sequential logic, such as true single phase clocking (TSPC) flip-flops, parallel counters and compressors have been proposed using MIGFETs [62,63]. Finally, the unique properties of RFETs, such as equivalence of pull-up and pull-down networks have led to some interesting applications in hardware security and resilience [64,65].…”
Section: Logic Circuits With Reconfigurable Field Effect Transistorsmentioning
confidence: 99%
“…RFET (figure 1(a)) can be configured as nMOS or pMOS device by applying an appropriate bias. This feature has been demonstrated to realize logic circuits with a lesser number of transistors compared to existing technology [4][5][6][7][8]. In literature, RFET has been demonstrated to implement logic gates with a lower transistor count i.e.…”
Section: Introductionmentioning
confidence: 99%